Humanising Library and Information Services: Role of the Library Profession - Gopinath, M. A. (Journal of Information and Knowledge, 1992)
Analyses the factors that call for humanising the library and information activities. Identifies the various aspects of information technology information service and information service that call for human knowledge and skills in serving the readers Presents Ranganathan's approach to these aspects of library service which is called Energising Library Service.